2003
DOI: 10.1007/s00122-003-1269-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL for growth- and grain yield-related traits in rice across nine locations of Asia

Abstract: Rice double-haploid (DH) lines of an indica and japonica cross were grown at nine different locations across four countries in Asia. Genotype-by-environment (G x E) interaction analysis for 11 growth- and grain yield-related traits in nine locations was estimated by AMMI analysis. Maximum G x E interaction was exhibited for fertility percentage number of spikelets and grain yield. Plant height was least affected by environment, and the AMMI model explained a total of 76.2% of the interaction effect. Mean envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
138
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 28 publications
19
138
0
1
Order By: Relevance
“…In this region, where SPIKE was identified, several QTLs for TSN have been detected, among which the alleles from japonica or tropical japonica cultivars increased TSN (30)(31)(32)(33)(34)(35)(36)(37)(38). Hitherto, no gene for TSN or grain yield in this cluster has been isolated (39).…”
Section: Discussionmentioning
confidence: 99%
“…In this region, where SPIKE was identified, several QTLs for TSN have been detected, among which the alleles from japonica or tropical japonica cultivars increased TSN (30)(31)(32)(33)(34)(35)(36)(37)(38). Hitherto, no gene for TSN or grain yield in this cluster has been isolated (39).…”
Section: Discussionmentioning
confidence: 99%
“…A comparative QTL analysis of rice heading-date QTL on the short arm of chromosome 1 reveals several other published QTL in the same region as dth1.1. Of 17 rice QTL studies examined Xiao et al 1995Xiao et al , 1996Xiao et al , 1998Kohn et al 1997;Lu et al 1997;Yano et al 1997;Doi et al 1998;Lin et al 1998;Xiong et al 1999;Maheswaran et al 2000;Bres-Patry et al 2001;Moncada et al 2001;Cai and Morishima 2002;Yu et al 2002;Hittalmani et al 2003;Septiningsih et al 2003), five heading-date QTL were identified in the dth1.1 region, four of which were detected in interspecific crosses in rice (Kohn et al 1997;Doi et al 1998;Xiao et al 1998;Cai and Morishima 2002) and one in an intraspecific cross (Maheswaran et al 2000). Interestingly, in the thoroughly studied intraspecific Nipponbare/Kasalath population, 14 heading-date QTL have been identified, none of which are located on chromosome 1 (Yano 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 80 QTLs for flowering time detected under well-watered conditions were collected from ten papers (Li et al 1995;Yano et al 1997;Lafitte and Courtois 1999;Lin et al 2000;Maheswaran et al 2000;Yamamoto et al 2000;Yu et al 2002;Hittalmani et al 2003;Lanceras et al 2004;Dong et al 2004). A total of 59 QTLs for plant height were collected from ten papers (Li et al 1995;Lafitte and Courtois 1999;Hemamalini et al 2000;Yu et al 2002;Courtois et al 2003;Hittalmani et al 2003;Lanceras et al 2004;Xu et al 2004;MacMillan et al 2006;Gomez et al 2006). All the QTLs are compiled in TropgeneDB.…”
Section: Evaluation Of Efficiency Of Meta-qtl Analysismentioning
confidence: 99%